PENERAPAN TEKNIK DIEGETIC SOUND DALAM TATA SUARA FILM “SAMSARA” - Agung Bima Susetyo Basuki; Nyoman Lia Susanthi; Gede Basuyoga Prabhawita (CALACCITRA: JURNAL FILM DAN TELEVISI, 2021)
The film "Samsara" is a fictional film inspired by a creator's anxiety about the characteristics of bullying that is increasingly occurring in the social environment in Indonesia. In order to create a film work requires the formation of audio visual. This is what underlies the author to discuss the application of diegetic sound-taking techniques to create film works. The creation of the fictional film "Samsara" uses a qualitative method of creation. Data relating to the aforementioned problems were collected using interview, observation, and literature study techniques. The data collected above is sharpened with audio theory, diegetic dimension theory, and non-diegetic dimension theory. The creators made this theory as study material according to their use in answering several things that could support the message and mood in the film "Samsara". The application of diegetic theory in the film "Samsara" which emphasizes atmosphere or ambiance as well as dialogue, monologues and others can be a builder of atmosphere and time and space indicators of a scene based on the setting of a scene, meaning that if there is a visual of a scene, there must be a sound that is served from the scene, thus supporting the need for narrative and story telling films that make it easier for the audience to digest the scenes in the film through audio. The output of this final project is an action drama genre, with a duration of twenty-four minutes, and has a target age from adolescence to adulthood. The film "Samsara" is a 2k (2.39: 1) digital cinema standard with a resolution of 2048x858.